2020
DOI: 10.1200/jgo.19.00111
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Prognostic Factors of Sunitinib as First-Line Therapy for Patients With Metastatic Renal Cell Carcinoma in an Arab Population

Abstract: PURPOSE Antiangiogenic tyrosine kinase inhibitors have been the mainstay first-line therapy for metastatic renal cell carcinoma (mRCC). We reviewed the efficacy of first-line therapy with sunitinib in patients with mRCC in an Arab population. METHODS Medical records of patients with mRCC treated at a tertiary care center in Saudi Arabia, during the period from 2007 to 2016, were reviewed. Demographic data, treatment received, response, and prognostic factors were analyzed. RESULTS Fifty-five patients who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…Of note, the lowest reported progressive disease rate in the contemporary studies was 13.7, observed in the CHECKMATE 9ER trial. 12 Additionally, the PFS duration of 16.5 months was more than double that of our historical control 23 and is similar to the PFS rate obtained with the new CPI-containing regimens. Despite this study being a phase I/II trial, the patients’ characteristics clearly represent an unselected group, with only 28% of the patients having an ECOG performance status of zero and only 12% in the favorable IMDC risk group.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Of note, the lowest reported progressive disease rate in the contemporary studies was 13.7, observed in the CHECKMATE 9ER trial. 12 Additionally, the PFS duration of 16.5 months was more than double that of our historical control 23 and is similar to the PFS rate obtained with the new CPI-containing regimens. Despite this study being a phase I/II trial, the patients’ characteristics clearly represent an unselected group, with only 28% of the patients having an ECOG performance status of zero and only 12% in the favorable IMDC risk group.…”
Section: Discussionsupporting
confidence: 80%
“…The study was later amended to a planned enrollment of 39 patients after the publication of the real-world data of sunitinib in our population, which showed a response rate of 30% and PFS duration of 6 months. 23 This number was based on the single-stage phase II design 24 to test a null hypothesis of H0: P ≤ .3 versus an alternative hypothesis of P ≥ .5 with a significance level of 5% and power of 80%, where P represents the response rate.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a direct comparison of the results with data from the literature is not possible. However, according to the results of one retrospective study, it has been shown that patients who start therapy within the first 100 days from the time of diagnosis have a statistically significant faster progression of the disease (18). In this study, 27% of patients permanently discontinued therapy due to disease progression or death for any reason within 12 months of initiating targeted therapy.…”
Section: Discussionmentioning
confidence: 61%
“…RCCs are generally divided into five subtypes: clear cell, papillary, chromophobe, collecting duct, and unclassified, among which the first three constitute the majority of RCCs ( Truong and Shen, 2011 ). Although advances in the medical and surgical management of RCCs have been made ( Rini et al, 2009 ; Bazarbashi et al, 2023 ), the outcomes associated with the tumor remain relatively poor ( Badran et al, 2020 ). Additionally, differentiating between different subtypes of RCC is still difficult.…”
Section: Aberrant Expression Of Claudins In Renal Cell Carcinomasmentioning
confidence: 99%